Reconciliation through Church Union in post-Apartheid South Africa: The Uniting Presbyterian Church in Southern Africa - Duncan, Graham (Verbum et ecclesia, 2005)
This paper will argue that the union which brought the Uniting Presbyterian Church in Southern Africa into being was based on an inadequate view of reconciliation in a Christian context. While lip service may have been paid to the authentic concept, flawed views have led to many misunderstandings concerning the mission and vision of the new church, and despite attempts at reformation and renewal, reconciliation as justice restored still evades the ethos of the young denomination.